Effect of problem-based learning on stages of change for exercise behaviour in patients with coronary artery disease. - Kamwendo K; Tingström P; Bergdahl B; Svensson E (Physiotherapy Research International, 2004)
BACKGROUND AND PURPOSE: Physical activity plays an important part in preventing coronary artery disease and is targeted in most rehabilitation and education programmes. The aim of the present study was to evaluate stages of change for exercise behaviour in patients with a recent event of coronary artery disease. METHOD: A randomized two-group, pre--post-test design was used. Fifty-seven subjects were included in the problem-based learning intervention group and 61 subjects were included in the traditional rehabilitation control group. Data were analysed by intention-to-treat. A single-item five-category scale, based on the 'Stages of Change' model was used to measure the level of exercise behaviour. The statistical analysis used two non-parametric approaches for ordered categorical data. RESULTS: There was a significant systematic change over time towards the extreme scale categories in both groups. This suggested that individuals who were inactive before the intervention regressed, whereas individuals with some interest in physical activity remained static or improved. No significant differences between groups were found. CONCLUSION: Problem-based learning did not significantly influence patients' progression through exercise behaviour stages. Rehabilitation teams should be observant of inactive participants and their greater risk of regression.